Neoadjuvant Immunotherapy and De-escalation of Surgery in Locally Advanced Breast Implant-associated Anaplastic Large Cell Lymphoma - Salgarello, Marzia; Krupa, Jaroslaw; Allchin, Rebecca; Pilgrim, Simon; Miall, Fiona; Napoli, Arianna Di; Martelli, Maurizio; Tarantino, Giulio (Archives of Plastic Surgery, 2024)
Breast implant-associated anaplastic large cell lymphoma (BIA-ALCL) is a rare form of non-Hodgkin T-cell lymphoma diagnosed in patients with a history of breast implants. Most patients develop a periprosthetic effusion at early stages of disease while less common presentations include a palpable mass, severe capsular contracture, lymphadenopathy, or cutaneous erythema. Due to the complex nature of this disease, a multidisciplinary approach is necessary for optimal management, particularly in locally advanced disease or inoperable patients. We present the successful use of neoadjuvant therapeutic protocols in two cases of locally advanced BIA-ALCL. The first case was a 52-year-old patient with a left breast mass-like stage III disease who underwent combined targeted immunotherapy and chemotherapy (brentuximab vedotin [BV]–cyclophosphamide, doxorubicin, prednisone [CHP]). Following a complete radiological and metabolic response, the patient underwent bilateral implant removal, right total intact capsulectomy, left en bloc capsulectomy, and skin resection from the left inframammary fold in continuity with the capsule. The second case was a 65-year-old patient with right breast swelling and mass-like stage IIA disease who received targeted immunotherapy, BV. Following a complete metabolic response, she underwent bilateral implant removal and en bloc capsulectomy. A literature review and the reported cases suggest the effectiveness of targeted immunotherapy as monotherapy or in combination with chemotherapy in locally advanced BIA-ALCL in disease downstaging, surgical de-escalation, reduction of significant postoperative complications, and an acceptable tolerance profile. Although surgery is an essential part of treatment, the timing and type of intervention should be carefully planned, especially when primary, radical resection is uncertain.
Keywords: brentuximab vedotin; breast implant-associated anaplastic large cell lymphoma; breast implant; neoadjuvant therapy; capsulectomy